(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Two years (2009-2010) experience of the experimental use of alternative energy sources in technological processes of agriculture is analyzed. Water was heated by an outside air heat pump with passive evaporators, and used for new born piglets resting place floor heating. Experimental data were obtained by the reckoning consumption of electric energy for the operation of the heat pump’s compressor and electric heater, and by a heat meter registering the consumed heat energy. The obtained data show that the outside air heat pump with passive evaporators is working successfully during summer months, when the coefficient of performance (COP) of the heat pump exceeds 3.5. When the outside temperature decreases under +10˚C, the heat pump evaporators become covered with hoarfrost and ice. The value of the COP and produced amount of heat energy reduce, and the electric heater often switches on. During the experimental research one of the heat pump evaporators was supplied with a ventilator, air flow from which was washing the surface of the evaporator’s plates. So the satisfactory operation of the heat pump was provided till December 10, 2009 and November 25, 2010.